Invasive vascular plant species in the south-western part of the Silesian Upland (south Poland) - Urbisz, Alina; Urbisz, Andrzej (Biodiversity: Research and Conservation, 2006)
The main goal of this study is to present a diversity of invasive plants occurring in the south-western part of the Silesian Upland and to estimate their impact on transformation of the native plant cover. Among 101 species considered to be invasive, three groups were distinguished: “not harmful” (46 species), “weeds” (32) and “transformers” (23). Subsequently, their characteristics is given (origin, geographical-historical groups, life forms, frequency of occurrence) and they are briefly compared. Special attention is paid to the species included in the “transformers” group which enter natural and semi-natural habitats and transform the native plant cover to the largest extent. It has been determined that these are usually large perennial plants or trees, of predominantly North American origin, with numerous localities in which they often form compact patches occupying large areas.